Fluoride Affects Enamel Protein Content via TGF-β1-mediated KLK4 Inhibition. (October 2014) - Suzuki, M.; Shin, M.; Simmer, J.P.; Bartlett, J.D.
Dental fluorosis is caused by chronic high-level fluoride (F – ) exposure during enamel development, and fluorosed enamel has a higher than normal protein content. Matrix metalloproteinase 20 cleaves enamel matrix proteins during the secretory stage, and KLK4 further cleaves these proteins during the maturation stage so that the proteins can be reabsorbed from the hardening enamel. We show that transforming growth factor β1 (TGF-β1) can induce Klk4 expression, and we examine the effect of F – on TGF-β1 and KLK4 expression. We found that in vivo F – inhibits Klk4 but not Mmp20 transcript levels. LacZ-C57BL/6- Klk4 +/L acZ mice have LacZ inserted in frame at the Klk4 translation initiation site so that the endogenous Klk4 promoter drives LacZ expression in the same temporal/spatial way as it does for Klk4. KLK4 protein levels in rat enamel and β-galactosidase staining in LacZ-C57BL/6- Klk4 +/L acZ mouse enamel were both significantly reduced by F – treatment. Since TGF-β1 induces KLK4 expression, we tested and found that F – significantly reduced Tgf-β1 transcript levels in rat enamel organ. These data suggest that F – -mediated downregulation of TGF-β1 expression contributes to reduced KLK4 protein levels in fluorosed enamel and provides an explanation for why fluorosed enamel has a higher than normal protein content.